المفردات الاصطلاحية من الكتاب "نحو ثقافة إسلامية أصيلة" لعمر سليمان الأشقر والاستفادة منها في إثراء لغة طلاب الكلية بجامعة الراية - Mufti Abdul Aziz (Rayah Al-Islam, 2019)
This research aims to analyze and limit terms vocabularies in the book "Nahw Tsaqȃfah Islȃmiyyah Ashȋlah" by Umar Sulayman Al-Asyqar, which the book is including of materials books for PBA (Arabic Education Department) in the STIBA Ar Raayah that contains many terms vocabularies. Aside from that, this research also aims to present effective ways to utilization of those vocabularies terms to enriching the students language in STIBA Ar Raayah. This research uses descriptive methods of analysis where researcher is trying to accumulate and limit terms vocabularies of that book and then analyse it by definition them according to etymologically and terminologic. In this study, two main results achieved; the first, that terms vocabularies in the book "Nahw Tsaqȃfah Islȃmiyyah Ashȋlah" numbered fifty-one vocabulary, which can be analyzed by defining each vocabulary etymologically and terminologis. Then the second, effective ways that proposed for utilization of the vocabulary to enrich the students language the STIBA Ar Raayah is in two ways; First, by way of formulating the learning material in the form of conversation come with reserved exercises for these lessons, and in the form of text reading is also equipped with with the exercises for it. And second, by way of formulating the dictionary of terms vocabularies for the book.